2020
DOI: 10.4067/s0717-75182020000200247
|View full text |Cite
|
Sign up to set email alerts
|

Early menarche and its association with anthropometric and body composition variables in young university students

Abstract: Objective: Evaluate the association between early menarche and anthropometric/body composition variables in young female university students. Methods: Cross-sectional study involving female university students at a public university in northeastern Brazil. Anthropometric and body composition data were collected, along with a self-report of age at menarche. The conceptual model considered demographic, socioeconomic and lifestyle variables as well as the perception of weight in childhood and at menarche. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Early menarche (EM), defined by at least one menstruation before the twelfth birthday of a girl (Arcoverde et al 2020;Must et al 2005) is reported to be associated with lower body height in comparison with peers of not early menarche (NEM) when socioeconomic and other environmental factors remain constant in both groups (Conway et al 2012;Kang et al 2019). A previous study also reported the association of EM with early age at peak height velocity and low leg length-to-sitting height ratio (Conway et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early menarche (EM), defined by at least one menstruation before the twelfth birthday of a girl (Arcoverde et al 2020;Must et al 2005) is reported to be associated with lower body height in comparison with peers of not early menarche (NEM) when socioeconomic and other environmental factors remain constant in both groups (Conway et al 2012;Kang et al 2019). A previous study also reported the association of EM with early age at peak height velocity and low leg length-to-sitting height ratio (Conway et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…EM acts as a risk factor for developing overweight and obesity in adolescence and adulthood (Martínez et al 2010;Rosenfield et al 2009). Several studies have examined issues regarding menarche and adiposity: Brazil (Arcoverde et al 2020), Iran (Pejhan et al 2013), Korea (Oh et al 2012), Kuwait (Al-Awadhi et al 2013), Mexico (Datta Banik et al 2015), Spain (Labayen et al 2009), and the USA (Adair and Gordon-Larsen 2001). However, it is not clear from the literature review whether obesity and higher body fat are the responsible factors for EM or earlier age at menarche (AM) plays an important role in the development of body fat and other health risks like cardiovascular diseases and even cancer in adulthood Dickinson 2014, 2016;Méndez-Domínguez 2011).…”
Section: Introductionmentioning
confidence: 99%